2014
DOI: 10.1016/j.foodchem.2013.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Isotope dilution liquid chromatography–tandem mass spectrometry for simultaneous identification and quantification of beta-casomorphin 5 and beta-casomorphin 7 in yoghurt

Abstract: A highly selective and sensitive liquid chromatography-tandem mass spectrometry method was developed and validated for the simultaneous identification and quantification of beta-casomorphin 5 (BCM5) and beta-casomorphin 7 (BCM7) in yoghurt. The method used deuterium labelled BCM5-d10 and BCM7-d10 as surrogate standards for confident identification and accurate and quantification of these analytes in yoghurt. Linear responses for BCM5 and BCM7 (R(2)=0.9985 and 0.9986, respectively) was observed in the range 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…βCM-7 was determined in whole pasteurized milk, ultra-heat treated milk, bottle-sterilized milk, fermented milks like yoghurt and probiotic fermented milk (Ul Haq et al, 2015). But it is reported that fermentation and storage reduced βCM-5 and βCM-7 concentration in yoghurt (Nguyen et al, 2014;Nguyen, 2015).…”
Section: β-Casomorphin7 (βCm-7)mentioning
confidence: 99%
“…βCM-7 was determined in whole pasteurized milk, ultra-heat treated milk, bottle-sterilized milk, fermented milks like yoghurt and probiotic fermented milk (Ul Haq et al, 2015). But it is reported that fermentation and storage reduced βCM-5 and βCM-7 concentration in yoghurt (Nguyen et al, 2014;Nguyen, 2015).…”
Section: β-Casomorphin7 (βCm-7)mentioning
confidence: 99%
“…A βcasomorphina-7 também pode ser encontrada em derivados do leite A1, tais como como iogurte e queijos [18,19] , embora seja proposto que certos micro-organismos presentes nestes produtos teriam a capacidade de hidrolisar o BCM-7 até peptídeos menores ou mesmo em aminoácidos [18] . Ainda não foi demostrado se tais micro-organismos também apresentam similar influência dentro do trato gastrintestinal [20] . Pode ser prospectado ainda, o potencial da microbiota intestinal humana em hidrolisar peptídeos bioativos, incluindo aqueles com atividade opioide.…”
Section: β-Caseína E Liberação De Bcm-7unclassified
“…There is now clear evidence that BCM-7 is released not only from milk but also from yoghurt and cheese, and in all likelihood any milk product [ 6 , 7 ]. There is also evidence that there is modest release of BCM-7 in the cheese- and yoghurt-making processes, but that during the latter, certain bacteria present in yoghurt may hydrolyze BCM-7 [ 15 , 16 ]. Whether such bacteria consumed in yoghurt also have a similar influence within the human gastrointestinal tract is unknown.…”
Section: Beta-caseins and Bcm-7mentioning
confidence: 99%